The World Trade Organization's Impact on Developing Countries: Opportunities and Challenges - Bobomurodova Mahliyo Rustam qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The impact of the World Trade Organization on developing countries is examined in this article. Although the main agenda of the WTO is to open world trade and improve trade conditions, its regulations sometimes cause trouble for the economies of developing countries. However, by being a member of the WTO, these countries achieve benefits such as increasing exports, receiving foreign investment, adopting technology, etc. According to the article, the opportunities and constraints of the WTO for developing countries are mentioned, and suggestions are given to these countries.